Bone Mineral Density in Children with Juvenile Idiopathic Arthritis: A Hospital Based Study (Bangladesh Journal of Child Health, 2013)
Background: Failure to develop adequate bone mineralization is common in children with Juvenile Idiopathic Arthritis (JIA). Osteopenia or osteoporosis occurs in all the JIA subtype but particularly common in systemic onset and polyarticular JIA. There is an association of increased demineralization of bones with duration of joint disease. Objective: To determine the extent of osteoporosis in Juvenile Idiopathic Arthritis (JIA). Methodology: Cross sectional study conducted from July 2011 to December2011 in Department of Paediatrics and Institute for Nuclear Medicine and Ultrasound(INMU), Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. Participants: Total 30 patients were enrolled in this study. Results: Significant osteopenia among 53.33% and 70% JIA patients and osteoporosis among 26.67% and 23.33% JIA patients were found at femur neck and lumber region respectively. In polyarticular cases majority of the cases had osteopenia (81.25% and 75%) and in systemic onset JIA cases majority had osteoporosis (55.56% and 33.37%) at femur neck and lumber region respectively. Longer duration cases at diagnosis had more osteopenia (58.33% and 66.67%) and osteoporosis (41.67% and 33.33%) than the shorter duration cases at femur neck and lumber region respectively. Conclusion: From this small pilot study it may be concluded that JIA Patients are likely to have low BMD. Among them polyarticular and systemic onset JIA patients are even more susceptible to low BMD. There is also positive relationship between the duration of arthritis and low BMD. DOI: http://dx.doi.org/10.3329/bjch.v37i1.15347 BANGLADESH J CHILD HEALTH 2013; VOL 37 (1) : 18-21